“LEARNING FOREIGN LANGUAGES IN EARLY AGES” (Ta'limning zamonaviy transformatsiyasi, 2024)
The article under discussion depicts the learning foreign languages from childhood. The article describes the benefits of studying second or third language at a young age and the ways of teaching it to children. The main attention is paid on the influences of learning foreign languages.